Synthesis of ultra-high molecular weight poly(methyl methacrylate) initiated by the combination of copper nanopowder with organic halides - Ming Yuan; Xiaofang Han; Zekai Zhang; Ruijia Wang; Shengrong Guo (BMC Chemistry)
Abstract In this study, organic halides, such as 2-bromobutane (C4H9Br), ethyl α-bromophenylacetate (BPA), ethyl 2-bromoisobutyrate (EBiB), and ethyl 2-bromopropionate (EBP) are utilized in conjunction with copper nanopowder (Nano-Cu) to initiate the polymerization of methyl methacrylate (MMA). Among these, BPA combined with nano-Cu exhibits the highest reactivity, resulting in the production of poly(methyl methacrylate) (PMMA) with a number-average molecular weight (M n) of 1.91 × 106 Da, a weight-average molecular weight (M w) of 3.46 × 106 Da, and a polydispersity index (PDI) of 1.81. A kinetic analysis of the polymerization reveals that the reaction orders for MMA, BPA, and nano-Cu concentration are 0.76, 0.49, and 0.77, respectively. The activation energy of the polymerization of MMA initiated by BPA is calculated to be 59.6 kJ/mol. The molecular weight of PMMA product is determined using gel permeation chromatography (GPC), while the structure of the synthesized PMMA is characterized through proton nuclear magnetic resonance (1H NMR). Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF) is employed to analyze the precise structure and molecular weight of PMMA. Additionally, the nano-Cu recovered after the polymerization is examined using X-ray photoelectron spectroscopy (XPS). An electron paramagnetic resonance (EPR) spectrometer is employed to detect the reaction intermediate formed during the polymerization. Results from MALDI-TOF, XPS and EPR reveal that the polymerization of MMA proceeds via a radical mechanism, with the combination of nano-Cu and BPA leading to the formation of BPA residual radicals that initiate the polymerization of MMA.